Dapagliflozin alleviates myocardial ischemia/reperfusion injury by reducing ferroptosis via MAPK signaling inhibition - Chen, Weixiang; Zhang, Yue; Wang, Zuoxiang; Tan, Mingyue; Lin, Jia; Qian, Xiaodong; Li, Hongxia; Jiang, Tingbo (Frontiers in Pharmacology, 2023)
Reperfusion is essential for ischemic myocardium but paradoxically leads to myocardial damage that worsens cardiac functions. Ferroptosis often occurs in cardiomyocytes during ischemia/reperfusion (I/R). The SGLT2 inhibitor dapagliflozin (DAPA) exerts cardioprotective effects independent of hypoglycemia. Here, we investigated the effect and potential mechanism of DAPA against myocardial ischemia/reperfusion injury (MIRI)-related ferroptosis by using the MIRI rat model and hypoxia/reoxygenation (H/R)-induced H9C2 cardiomyocytes. Our results show that DAPA significantly ameliorated myocardial injury, reperfusion arrhythmia and cardiac function, as evidenced by alleviated ST segment elevation, ameliorated cardiac injury biomarkers including cTnT and BNP and pathological features, prevented H/R-triggered cell viability loss in vitro. In vitro and in vivo experiments showed that DAPA inhibited ferroptosis by upregulating the SLC7A11/GPX4 axis and FTH and inhibiting ACSL4. DAPA notably mitigated oxidative stress, lipid peroxidation, and ferrous iron overload and reduced ferroptosis. Subsequently, network pharmacology and bioinformatics analysis suggested that the MAPK signaling pathway was a potential target of DAPA and a common mechanism of MIRI and ferroptosis. Importantly, DAPA treatment significantly reduced MAPK phosphorylation in vitro and in vivo, suggesting that DAPA might protect against MIRI by reducing ferroptosis through the MAPK signaling pathway.